Inside Cover: Unprecedented Noncanonical Features of the Nonlinear Nonribosomal Peptide Synthetase Assembly Line for WS9326A Biosynthesis (Angew. Chem. Int. Ed. 36/2021). Issue 36 (21st June 2021) - Kim, Myoun‐Su; Bae, Munhyung; Jung, Ye‐Eun; Kim, Jung Min; Hwang, Sunghoon; Song, Myoung Chong; Ban, Yeon Hee; Bae, Eun Seo; Hong, Suckchang; Lee, Sang Kook; Cha, Sun‐Shin; Oh, Dong‐Chan; et al.
Abstract : The understanding of the biosynthetic logic of nonlinear nonribosomal peptide synthetases (NRPSs) provides potentially valuable tools for the engineering of diverse NRPs. In their Research Article on page 19766, Sun‐Shin Cha, Dong‐Chan Oh, Yeo Joon Yoon et al. elucidate the unprecedented features of a NRPS assembly line from marine Streptomyces that involves the shuttling of amino acids from two stand‐alone adenylation (A)–thiolation (T) didomain modules to the iteratively operating condensation (C)–T didomain by two type II thioesterases (TEs).